Labor market effects of immigration: Evidence from neighborhood data - Thomas K. Bauer; Regina Flake; Mathias G. Sinning (Institute for the Study of Labor (IZA), 2011)
This paper combines individual-level data from the German Socio-Economic Panel (SOEP) with economic and demographic postcode-level data from administrative records to analyze the effects of immigration on wages and unemployment probabilities of high- and low-skilled natives. Employing an instrumental variable strategy and utilizing the variation in the population share of foreigners across regions and time, we find no support for the hypothesis of adverse labor market effects of immigration.
urn:nbn:de:101:1-201105306310
Keywords: F22; J31; J64; R23; 330; international migration; effects of immigration